Applicable Law in Validity of Arbitration Clause: Judicial Practices of the US Courts on Charterparty Disputes - Jiaming Zhang (Studies in Law and Justice, 2023)
Incorporating the arbitration clause of charterparty into bills of lading (incorporation clause) is widely used in practice. When the rightful holder of bills of lading, usually the consignee, claims cargo damage to carrier, a valid arbitration clause rejects jurisdiction of domestic courts, or it will result in the jurisdiction of an arbitration tribunal. Determining governing law of examining arbitration clause, therefore, is the prerequisite of such cases. Choice of law turns out to be a controversial legal problem on account of either absence of uniformed legislation, or the complicated nature of relevant dispute. Generally, potential choices include governing law of charterparty, of bills of lading, or lex fori. In accordance with judicial practices in the United States, various courts prefer different governing law choices, but considering the interests balance between consignee and carrier, as well as party autonomy of commercial activities, the United States provides with the international society its inclination that governing law of bills of lading shall be applied.